2013
DOI: 10.1080/10810730.2013.778363
|View full text |Cite
|
Sign up to set email alerts
|

Men's and Women's Responses to Two-Sided Health News Coverage: A Moderated Mediation Model

Abstract: This study explores how audiences respond to news coverage of food and nutrition topics when that coverage provides either 2-sided (positive and negative) information or 1-sided, unanimously positive information. A moderated mediation model helps clarify the different impacts of 2- and 1-sided news coverage and the psychological processes they elicit. Specifically, gender moderates the relative effects of 1- and 2-sided news stories; ambivalent feelings play a mediating role in the process. The findings confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…In two experimental studies, participants read either a one-sided story that discussed positive research findings about and/or positive health outcomes associated with a food or supplement (e.g., tofu, vitamin B6, milk), or a two-sided story that provided both positive and negative findings and/or outcomes associated with the food/supplement (Chang, 2013, 2015). Chang (2013) found that exposure to two-sided nutrition information increased ambivalence about consuming the food/supplement in question, increased negative attitudes toward the advocated food/supplement, and decreased intentions to consume the advocated food/supplement. She also found that two-sided exposure increased uncertainty about health research, increased negative attitudes toward health research, and lowered perceptions of news credibility (Chang, 2015).…”
Section: Contradictory Information: Conceptualizations and Evidence Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In two experimental studies, participants read either a one-sided story that discussed positive research findings about and/or positive health outcomes associated with a food or supplement (e.g., tofu, vitamin B6, milk), or a two-sided story that provided both positive and negative findings and/or outcomes associated with the food/supplement (Chang, 2013, 2015). Chang (2013) found that exposure to two-sided nutrition information increased ambivalence about consuming the food/supplement in question, increased negative attitudes toward the advocated food/supplement, and decreased intentions to consume the advocated food/supplement. She also found that two-sided exposure increased uncertainty about health research, increased negative attitudes toward health research, and lowered perceptions of news credibility (Chang, 2015).…”
Section: Contradictory Information: Conceptualizations and Evidence Fmentioning
confidence: 99%
“…Both quantitative and qualitative studies have found that people perceive conflict about these and other topics (Carpenter, Elstad, Blalock, & DeVellis, 2014; Vardeman & Aldoory, 2008), which may drive them to seek more information (Weeks, Friedenberg, Southwell, & Slater, 2012) and influence their behavior decisions (Gibson et al, 2015). Yet few studies have explicitly assessed media exposure to contradictory information (Nagler, 2014; Nagler & Hornik, 2012; Tan, Lee, & Bigman, 2015), and research examining the effects of such exposure is limited (Chang, 2013, 2015; Dixon & Clarke, 2012; Jensen & Hurley, 2012; Nan & Daily, 2015). Health and scientific controversies are increasingly prominent in the media.…”
mentioning
confidence: 99%
“…Furthermore, males, people with differing levels of perceived vulnerability, and those from other geographic locations may respond differently to HIV test messages. A recent study, for instance, found that men and women responded in opposite directions to two-sided messages related to news coverage [ 25 ]. In another study, induction of mortality salience increased rates of HIV testing, but only among those who were exposed to a message that increased their feelings of vulnerability to HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Although researchers are well prepared to make sense of evolving scientific evidence and health recommendations, the public may struggle to do so, due in part to limited literacy about scientific research [11]. Several experimental studies have found that exposure to conflicting health information produces negative emotional reactions to such content (such as frustration, annoyance, and distress) [9] and undesirable cognitive outcomes, including confusion (perceived ambiguity about the health topic in question or health research in general) [8][9][10], backlash (negative beliefs or attitudes toward the health topic in question or health research in general) [10,44], and attitudinal ambivalence (positive and negative evaluations of a given object at the same time) [9,44]. Moreover, there is some evidence that these affective and cognitive responses could translate into behavioral effects [8].…”
Section: Plos Onementioning
confidence: 99%